The logistics as a driving force of trade between Latin America and Asia. Case study on the ports of Callao, Valparaíso, Busan and Shenzhen (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
Within the dynamics of a global economy with efficient markets in constant transformation, commercial initiatives are a fundamental component for the socioeconomic development of countries. On this basis, this study analyzes management of the port environment and its impact on regional and national development for the cases of the ports of Callao, Valparaíso, Busan and Shenzhen; In so doing, the study focuses on best practices geared towards strengthening trade relations and how these facilities drive trade, resulting in an increase in the trade flow between countries. Methodologically, this is a descriptive-documentary study with a non-experimental design. The main results of logistics best practices are presented: they include the creation of a single window for port procedures, the strengthening of relations between actors related to trade and port operation, and the establishment of the port authority as the highest body for management and integration with the cities and the areas of influence.
Keywords: port management; economic and social development; commercial relations